Local dimension of fractal measure asociated with the (0, 1, a) - Problem the case a = 6 - Son, Le Xuan; Trinh, Pham Quang; Thanh, Vu Hong (VNU Journal of Science: Mathematics - Physics, 2005)
Abstract